2021
DOI: 10.48550/arxiv.2112.11665
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SMEFTs living on the edge: determining the UV theories from positivity and extremality

Abstract: We study the "inverse problem" in the context of the Standard Model Effective Field Theory (SMEFT): how and to what extend can one reconstruct the UV theory, given the measured values of the operator coefficients in the IR? The main obstacle of this problem is the degeneracies in the space of coefficients: a given SMEFT truncated at a finite dimension can be mapped to infinitely many UV theories. We discuss these degeneracies at the dimension-8 level, and show that positivity bounds play a crucial role in the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…The former method involves constructing the group projectors of irreducible representations from the Clebsch-Gordon coefficients and is very effective for a problem with sufficient symmetries and a manageable number of degrees of freedom, while the latter is useful for generic problems that lack sufficient symmetries and consequently, the bounds are only extracted numerically in general. It is found that only a small fraction of the parameter space of the SMEFT is consistent with the positivity bounds, as discussed in [31][32][33][34][35][36] for the example of constraining the anomalous quartic gauge couplings from vector boson scatterings. In [3], it was found that future electron-positron colliders can be used to probe violations of positivity bounds or the fundamental principles of quantum field theory up to the multi-TeV scale, regardless of the presence of dim-6 operators.…”
Section: Introductionmentioning
confidence: 62%
“…The former method involves constructing the group projectors of irreducible representations from the Clebsch-Gordon coefficients and is very effective for a problem with sufficient symmetries and a manageable number of degrees of freedom, while the latter is useful for generic problems that lack sufficient symmetries and consequently, the bounds are only extracted numerically in general. It is found that only a small fraction of the parameter space of the SMEFT is consistent with the positivity bounds, as discussed in [31][32][33][34][35][36] for the example of constraining the anomalous quartic gauge couplings from vector boson scatterings. In [3], it was found that future electron-positron colliders can be used to probe violations of positivity bounds or the fundamental principles of quantum field theory up to the multi-TeV scale, regardless of the presence of dim-6 operators.…”
Section: Introductionmentioning
confidence: 62%
“…In tree-level UV completions, an extremal ray corresponds to a UV particle with fixed SMEFT quantum numbers, while a ray inside the cone, on the other hand, would indicate presence of multiple UV states. Therefore, positivity bounds can provide important information to reverse-engineer the UV model from the SMEFT data [142,144,[166][167][168]. On the other hand, confronting the experimental data with positivity bounds on dimension-8 operators can also be used to put exclusion limits on relevant BSM physics unambiguously, while excluding dimension-6 operators to a certain energy scale would be ambiguous.…”
Section: Applications To Smeftmentioning
confidence: 99%
“…On the other hand, confronting the experimental data with positivity bounds on dimension-8 operators can also be used to put exclusion limits on relevant BSM physics unambiguously, while excluding dimension-6 operators to a certain energy scale would be ambiguous. This is because a dimension-6 coefficient can vanish due to cancellations between multiple UV states, but that is not possible for a dimension-8 coefficient [144,168]. An intriguing observation is that among the seesaw mechanisms only the heavy right-handed neutrino in the type-I model reaches the extremity of the positivity cone [169], which means that the SMEFT can be used to pin down the seesaw mechanism if it is indeed type-I.…”
Section: Applications To Smeftmentioning
confidence: 99%
“…In the case of a treelevel UV completion, each of these ERs represents a UV particle with specific quantum numbers or symmetry structure that is a projection of the symmetry of UV theory to that of the SM [8]. (For a loop-level UV completion, an ER may not directly correspond to the UV particle but becomes a component of the UV loop [34].) This implies that the convex cone bounds, or the dim-8 operators, are valuable and pertinent to the inverse-problem of reverse-engineering the UV model from a set of measured Wilson coefficients.…”
Section: Positivity Cone and The Inverse Problemmentioning
confidence: 99%
“…The fact that the extremal rays of the positivity cone are the group projectors of irreducible representations in the product decomposition of the symmetries of an EFT implies that positivity bounds can be used to infer the UV states [8]. This is most significant if experiments were to find some new physics located close to the boundary of the positivity cone, or even better, close to one of its extremal rays [3,34]. In these favorable circumstances, com-paring the positivity cone with the experimental data would enable the model-independent inference of UV particles' quantum numbers.…”
Section: Introductionmentioning
confidence: 99%